A Topologia poética de Emmanuel Hocquard - Santos, Marília Garcia (2010)
The objectives of this research were to map out some of the displacements found on the work of the French poet Emmanuel Hocquard, based on aspects belonging to his texts construction and also on the way the author deals with space related subjects: travels, spacial and temporal displacements, landscapes, the space of writing. To manage that, it was shown that the displacement is configured, basically, in two directions: one of them being a close-to-far way and the other a far-to-close way. On the first way there is an opposition to a frozen language and the endeavour to create distance, be it concerning the relationship between the private and subjective spheres or concerning the language commonplaces. These questions were focused following some recurring concepts on the discussion about contemporary poetry, such as literality and the double lyricism-antilyricism, as well as the author s precious theoretical appointments. Moreover, his use of the lyric labels , or in another words, of ocidental lyric forms and practices and the thecnique of collage, was also analyzed On the second way, Hocquard s attempts to recollect the past, his private life and his reminiscences are seen while he searches for writing topics that can be rethought and updated. On this direction, there is his in loco return to Tanger, the city where the author spent his childhood years. Beyond that, Hocquard s workings with translation, the act of bringing the (far) language close, and his grammar writing experiments can be found on this movement. The aforementioned displacements contributes to the disposable and everchangin aspects of his textes. Given the importance of translation in the author s work, the second part of this research is exclusively composed of translations of the quoted and studied texts.